If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 = 2x + 15 Reorder the terms: 13 = 15 + 2x Solving 13 = 15 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 13 + -2x = 15 + 2x + -2x Combine like terms: 2x + -2x = 0 13 + -2x = 15 + 0 13 + -2x = 15 Add '-13' to each side of the equation. 13 + -13 + -2x = 15 + -13 Combine like terms: 13 + -13 = 0 0 + -2x = 15 + -13 -2x = 15 + -13 Combine like terms: 15 + -13 = 2 -2x = 2 Divide each side by '-2'. x = -1 Simplifying x = -1
| -2(2x+4)=-16 | | 2x-21-x+10=-1 | | 3(x+8)=45 | | 7(1+2x)=147 | | -6=11x-5x | | 5x+2(6)=3x(11) | | 15=5-2x | | 6(2x+7)=126 | | -4(-2+5x)=28 | | X^2+4xy+5x=0 | | (-3)/(-10)*0*(-2)= | | -5(7+7x)=-105 | | 3x+12-4x=20 | | 8x+7=x-1 | | -4(-7+6x)=-236 | | x^2+-20x+39=0 | | d^2+8c+12=0 | | -4+4x=2x+14 | | 6x+6=-2+7x | | 5x^2-22=0 | | 2x-7=7x-32 | | 15.4c-13.7=14x-17.2 | | -4+7X=-2x-94 | | 6x+6=-4x+6 | | 4(3+2x)-7= | | (-21)/3-5*(-5)= | | 4y+16x=20 | | .75(x+2)-(2/3)(x-3)=2 | | 4x-115=95-11x | | 3y=9x-3 | | 6x+10=x+60 | | (2d+1)/3=6 |